Analysis of powder rheometry of FT4: Effect of particle shape. (14th December 2017) - Nan, Wenguang; Ghadiri, Mojtaba; Wang, Yueshe
Graphical abstract: Highlights: Effects of particle shape on FT4 powder rheometry are analysed. A mathematical model is proposed to predict the flow energy of binary mixture. The flow energy and bulk friction coefficient are sensitive to particle shape. The flow energy correlates well with the shear stress in front of the blade. Abstract: Particle shape has a strong influence on bulk powder flow and its associated rheology. It promotes mechanical arching and adversely affects fast feeding and dosing. We use the FT4 powder rheometer of Freeman Technology to experimentally characterise the particle flow as a function of the shear strain rate, and to predict its dynamics for rod-shape particles using the discrete element method. The results show a strong realignment of the orientation of particles in the horizontal plane as the bed is sheared by the blade motion. The flow energy required for agitating a bed of rodlike particles is much larger than that of spheres and it increases with the aspect ratio, due to a combined effect of the coordination number and excluded volume. The flowability of rodlike particles can be improved by the addition of spheres, and can be well predicted by the mathematical model developed in this work. The bulk friction coefficient of the binary mixture is a linear function of the volume fraction of its components. The flow energy correlates well with the shear stress arising in front of the blade, considering the effect of the bulk friction coefficient.